How Do Leaders and their Teams Bring about Organizational Learning and Outcomes?. Issue 1 (17th February 2014) - Berson, Yair; Da'as, Rima'a; Waldman, David A.
<x xml:space="preserve">Abstract</x> How do leaders generate a learning climate that yields favorable organizational outcomes? To address this question, we offer and test a model linking charismatic leadership with the team‐emergent states of shared vision and trust within the team, as predicting organizational learning climate, and long‐term assessments of organizational outcomes by key stakeholders. We examined this model in a sample of 69 Arab elementary schools in Israel using multiple sources of raters, predicting long‐term assessments by key stakeholders of respective schools (parents and superintendents) at 2 points in time: 1 year and 3 years following the survey of the teachers. In line with our expectations, we obtained an overall, indirect effect between charismatic leadership and organizational learning climate. We also found support for both the direct and indirect effects of leader charisma through trust within the team on organizational learning climate and school outcomes. Although charismatic leadership predicted shared vision among team members, shared vision did not predict organizational learning climate, and hence, our proposed mediating effects of shared vision on organizational learning climate and outcomes were not supported. We discuss both theoretical and practical implications for the effects of leaders on learning processes and outcomes.